2011
DOI: 10.1007/s10701-011-9606-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Geodesic Nature of Wegner’s Flow

Abstract: Wegner's method of flow equations offers a useful tool for diagonalizing a given Hamiltonian and is widely used in various branches of quantum physics. Here, generalizing this method, a condition is derived, under which the corresponding flow of a quantum state becomes geodesic in a submanifold of the projective Hilbert space, independently of specific initial conditions. This implies the geometric optimality of the present method as an algorithm of generating stationary states. The result is illustrated by an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The WWF ensures V (β) → 0 monotonically; in particular, the decay of off-diagonal elements of H(β) scales exponentially with [β] = energy −2 [28,40]. Moreover, the WWF induces a geodesic flow with respect to the Fubini-Study metric given appropriate constraints on H 0 and {ψ 0 } [28].…”
Section: Wegner Wilson Flow and Mblmentioning
confidence: 99%
See 2 more Smart Citations
“…The WWF ensures V (β) → 0 monotonically; in particular, the decay of off-diagonal elements of H(β) scales exponentially with [β] = energy −2 [28,40]. Moreover, the WWF induces a geodesic flow with respect to the Fubini-Study metric given appropriate constraints on H 0 and {ψ 0 } [28].…”
Section: Wegner Wilson Flow and Mblmentioning
confidence: 99%
“…The WWF ensures V (β) → 0 monotonically; in particular, the decay of off-diagonal elements of H(β) scales exponentially with [β] = energy −2 [28,40]. Moreover, the WWF induces a geodesic flow with respect to the Fubini-Study metric given appropriate constraints on H 0 and {ψ 0 } [28]. Numerical studies have demonstrated the WWF generally produces more quasilocal (in the sense of support on the lattice) integrals of motion in the MBL phase than other flow equation methodologies [18,41].…”
Section: Wegner Wilson Flow and Mblmentioning
confidence: 99%
See 1 more Smart Citation
“…The flows reviewed in her paper are summarized in table I. In conjunction with equation (7), the polar forms of these generators make it apparent why they must induce evolution towards a diagonalized Hamiltonian. * The function atan2 has the minor advantage over the usual inverse tangent that there is no ±π ambiguity.…”
Section: Choice Of Generatormentioning
confidence: 99%
“…They have also been analyzed in terms of geodesic flows. 7 Interest in CUTs has increased recently due to the discovery that they may provide physical insights when applied to important many-body problems such as the poorly understood phenomenon of many-body localization (MBL). 8,9 The study of MBL has exploded since Basko, Aleiner, and Altshuler published their seminal diagrammatic analysis of the phenomenon in 2006 10 .…”
Section: Introductionmentioning
confidence: 99%